Sobre terminología errónea en publicaciones entomológicas - Hilje, Luko (Universidad de Costa Rica, 2011)
A glossary is presented, despite being a non-exhaustive one, which includes a little more than one hundred terms frequently misused in entomological publications. They are organized in accordance to their degree of acceptance by the Real Academia Española. Each one is accompanied by its correct alternative (sometimes with a brief justification of the suggested term), and its proper use is illustrated with an example. Moreover, in addition to idiomatic mistakes themselves, a brief list of rather common conceptual mistakes is included, which correct use is explained.